Urgensi Manajemen Sarana dan Prasarana di Pondok Pesantren Modern - Adawiah, Diah Robiatul; Rijal Firdaos; Fandy Adpen Lazzavietamsi (EduInovasi: Journal of Basic Educational Studies, 2025)
The success of a process of educational or learning activities in schools is greatly influenced by the state of educational facilities and infrastructure owned by the school and the management of infrastructure facilities carried out. This study aims to examine the importance of facility and infrastructure management in modern Islamic boarding schools. This research was carried out qualitatively using a literature study approach. Data was collected from various books and journals. The various literature collected was carried out by descriptive analysis. This shows the urgency of facility and infrastructure management in the regulation and management of infrastructure in Islamic boarding schools. The management of educational facilities and infrastructure includes the process of planning, procurement, operation, inventory, maintenance and removal. To demonstrate the principles of managing educational facilities and infrastructure, there are principles that need to be considered so that these goals can be achieved optimally, namely the principle of achieving goals, the principle of efficiency, the principle of administrative, the principle of clarity of responsibility, and the principle of cohesiveness. Therefore, it is important for pesantren managers to pay more attention to the management and maintenance of facilities so that they can be used optimally and contribute to improving the quality of education.